Ecological Study of the Vegetation in the Loka Abaya National Park, Ethiopia - Assegid Assefa; Tamrat Bekele; Sebsebe Demissew; Tesfaye Abebe (International Journal of Forestry Research, 2024)
An ecological study of the vegetation in the Loka Abaya National Park, in the Central Rift Valley of Ethiopia, was conducted. Vegetation data and some environmental variables including physical and chemical properties of the soil, altitude, slope, and ecological disturbance were collected and subjected to the agglomerative hierarchical classification and ordination with the canonical correspondence analysis. For each of the community groups, the mean and standard errors were calculated from the environmental parameters to characterize the community types and quantitative relationships between environmental variables were analyzed by calculating Pearson’s product-moment correlation coefficient using the SAS computer software programme. A total of 198 plant species representing 79 families and 139 genera were collected and documented. Seven plant community types, namely, Vachellia brevispica Harms–Rhus natalensis Krauss, Ficus sur Forssk.–Vachellia albida (Del.) A. Chev., Panicum subalbidum Kunth–Cyperus latifolius Poir, Dodonaea angustifolia L. f.–Ximenia americana L., Combretum molle R.Br ex. G.Don–Combretum collinum Fresen., Ilex mitis (L.) Radlk–Olea europaea L. subsp. cuspidata, and Dichrostachys cinerea (L.) Wight & Arn, were identified. Ilex mitis–Olea europaea L. subsp. cuspidata community had the highest species richness, whereas the least species richness was recorded for the Panicum subalbidum–Cyperus latifolius community. The results of vegetation-environment relationships indicated that the measured environmental variables explained 74.99% of the total variation in floristic data. The results of the canonical correspondence analysis (CCA) of community-environment relationships indicated that among measured environmental variables, altitude (r2 0.0548, P<0.01), slope (r2 = 0.0241, P<0.01), pH (r2 = 0.01855, P<0.01), sodium (r2 = 0.01316, P<0.04), CEC (r2 = 0.01424, P<0.03), magnesium (r2 = 0.01282, P<0.04), potassium (r2 = 0.0152, P<0.02), and soil moisture content (SMC) (r2 = 0.01537, P<0.05) significantly explained the variation in species composition of the communities and their distribution. Therefore, ecosystem-oriented biodiversity conservation and restoration strategies will be implemented by considering these significant environmental variables.